Post-crisis LGBTQ film- and video-making in Spain: two case studies. (3rd July 2017) - Perriam, Chris
ABSTRACT: This essay is concerned with the ways in which the social, political and economic aftermath of the 2007–2008 global financial crisis has shaped small-scale, independent film- and video-making in Spain, specifically by LGBTQ artists. Exploring two autonomous author–producer–agencies – Emociones Produce/WeShoot Agencia Visual/Juanma Carrillo and Volando Vengo-Moviethinking/Rut Suso – it considers their strategies in relation to processes of austerity and attrition, circa 2012 to 2016. The main concern is with alterations in forms of expression in a directly visual sense but also in forms of professional survival; detailed analysis of these aspects is undertaken in order to nuance understandings of the cultural effects of crisis and post-crisis in Spain. The essay covers both niche queer video and the imagery of social and commercial entrepreneurialism. Where Emociones Produce/Carrillo's work is marked by the image of the vulnerable body and a mood of disruption, the varied image work of Volando Vengo-Moviethinking/Suso places commercial and social commitments in a tensive relationship with artistic demands in a bricolage of social-entrepreneurial, creative and pragmatic effects. Attending to crossovers in both case studies between art making, filmmaking and commissioned publicity helps add detail to the map of the processes of crisis and post-crisis in Spain in recent years.